(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article focuses on the fact that the speech of the section on the syntactic level of the Uzbek language and its position in the construction of the traditional complement to the point of view in the most acute theoretical aspect.